Role of beneficial fauna, associated to a silvopastoral system of Tithonia diversifolia cv. ICA Cuba oc-10, on the incidence of pest insects - Valenciaga, Nurys; Iraola, J.; Herrera, Magaly; E. Ruiz, T. (Cuban Journal of Agricultural Science, 2024)
To evaluate the beneficial fauna associated with a silvopastoral system of Tithonia diversifolia cv. ICA CUBA Oc-10, together with natural and improved grasses, and to determine their role in the incidence of insect pests, periodic random samplings were carried out (January, May and September). A sample of 20 raids was taken for each plant component. There was a lower proportion of phytophagous insects associated with the silvopastoral system with tithonia (9.97) compared to the base grass (19.13) and the control area (20.14) and, in turn, a higher proportion of bioregulators, with higher values ​​in tithonia (9.63) in contrast to the base grass (5.94) and control (3.84). Over time, phytophagous insects decreased significantly in the silvopastoral system with tithonia (3.70), with differences in base grass (9.18) and control area (12.52). Bioregulators remained stable in the beneficial fauna associated with tithonia (9.81), although without statistical differences among the rest of plant communities. It is concluded that there is a marked influx of bioregulatory organisms associated with the silvopastoral system with tithonia and base grass compared to the control area, with grasses only. An increase or stability was achieved with the years of exploitation of the system. This is a favorable indicator, which increases zoological and functional biodiversity, contributes to the integral management of insect pests and guarantees the sustainability of the agroecosystem. It is recommended to promote increasingly diversified areas, such as silvopastoral systems, and avoid the extension of monoculture areas to favor the balance between phytophagous and bioregulatory species, under non-harmful levels.